Effectiveness of virtual education on health care practitioners' self-efficacy in the neonatal unit - Maliheh Kadivar; Niama Seyedfatemi; Mitra Zolfaghari; Abbas Mehran; Tahereh Nikdel (Tehran University of Medical Sciences, 2017)
Background & Aim: Caregivers' education should be an active and dynamic process. Updated training programs are essential. This research was conducted to assess the effectiveness of virtual education on health care practitioners' self-efficacy in the neonatal unit. Methods & Materials: In this quasi-experimental research, hospitals affiliated with Tehran University of Medical Sciences that had level one neonatal unit were divided into two intervention and control groups. Sampling was conducted based on the inclusion criteria from all the nurses and midwives who were employed at these units. The intervention group received two months of asynchronous virtual education using learning management system. The control group did not undergo any specific training program. Data of both groups were collected using demographic questionnaire and Schwarzer & Jerusalem' Generalized Self-Efficacy Scale (GSE10) at the first day of the study and two months after the start of the intervention in the form of pre-test and post-test and were statistically analyzed. Results: Both of the intervention and control groups were similar regarding their demographic variables. Results showed that there was no significant difference between the mean score of self-efficacy of the two groups before the intervention (p=0.717); but there was a significant difference between the mean score of self-efficacy of two groups after the intervention (P <0.001). ANOVA test was used to eliminate the effect of pre-test score. Conclusion: The results of this research demonstrated that virtual education programs are effective in increasing the health care practitioners' self-efficacy at level one neonate units. As a result, applying this method of education is recommended to managers and training planners.